A PEMANFAATAN MEDIA GAMBAR DALAM PEMBELAJARAN METAMORFOSIS HEWAN DI SEKOLAH DASAR - Dina Aulia Putri; Muhammad Suwignyo Prayogo; Zahratul Imananda; Jova Resti Asyia Bilillah (TUNAS : Jurnal Pendidikan Biologi, 2026)
This study was conducted to address the low level of elementary school students’ understanding of animal metamorphosis concepts, which require visualization to facilitate comprehension. The purpose of this study was to examine the use of picture media in teaching animal metamorphosis at the elementary school level. The research employed a descriptive qualitative method with a literature study approach. The data sources consisted of secondary data obtained from scientific journals, books, and articles related to the research topic. Data were collected through documentation techniques and analyzed using content analysis, including data selection, data presentation, and conclusion drawing. Data validity was ensured through source triangulation. The results of the literature review indicate that the use of picture media helps students understand the stages of animal metamorphosis more concretely, increases their attention and learning interest, and assists teachers in delivering the material effectively. Therefore, picture media has proven to be an effective tool for supporting the learning process of animal metamorphosis in elementary schools.